Destitute and vulnerable- Fear of crime and victimisation among the homeless in urban and rural settings in South Africa (The Strategic Review for Southern Africa, 2021)
In 2019, the murders of five homeless men in Pretoria drew attention to the vulnerability of people living on the street. Despite more than two decades of democracy, social injustices and inequality continue to characterise post-apartheid South Africa. In addition to rampant poverty burgeoning informal settlements and poor housing, homelessness forms an integral part of the country’s urban and rural landscapes. However, homelessness is often accompanied by victimisation, racial and social injustices, and human rights violations. This paper reports on the victimisation of homeless people in South Africa, their patterns of reporting such incidences, and interactions with criminal justice agents. The paper also contextualises a fear of crime among the homeless and evaluates the limitations of the lifestyle exposure, routine activities, and deviance place theories to adequately explain injustices committed against the homeless. Implications for context-specific and global realities regarding homeless people are discussed. Quantitative data was obtained through non-probability sampling strategies from 40 urban and 30 rural homeless people. More than half of respondents felt unsafe while living on the streets (55.8%), feared becoming a victim of crime in the next year (54.5%) and the greater proportion of respondents (57.1%) had fallen victim to crime in the past. Statistically significant differences (p<0.05; r>0.4) featured between urban and rural respondents in terms of theft and harassment and anticipating victimisation. The findings highlight the social injustices suffered by homeless people, often at the hand of those who are supposed to protect vulnerable groups.